Unfulfilled Promises: Tensions in Mission Statements of For-Profit Colleges and Universities - Jake D. Winfield; Catherine Pressimone Beckowski (Ali Khorsandi Taskoh, 2023)
While collegiate missions of non-profit institutions have been extensively studied, missions of for-profit colleges in the United States have received less attention. This study examines the mission statements of 98 degree-granting for-profit colleges to articulate how these colleges describe the educational opportunities available to students. Our conventional content analysis found that these institutions emphasize career training, student learning experiences, student outcomes, and post-graduation opportunities. These findings suggest that FPCU missions may reflect isomorphic practices that allow FPCUs to compete with non-profit institutions in the higher education market. Furthermore, we propose that the unique career focus in FPCU missions may reflect credentialing theory, which suggests that the credential students earn, rather than the knowledge they attain, is what will enable success in the job market-a claim that is at odds with prior research indicating that FPCU graduates earn less, receive fewer interviews, and carry more debt than graduates of non-profit colleges. We argue that the language of FPCU missions highlights these institutions' contradictory aims of seeking profit while promoting access and success for students. We advance a deeper understanding of these institutions' self-ascribed purposes so that policymakers can ensure adequate student protections at for-profit colleges.